Strategi Konservasi Mengurangi Dampak Overpopulasi Monyet Ekor Panjang (Macaca fascicularis) yang Mengganggu Ekosistem dan Pertanian di Pulau Lombok - Krisna Wijaya; Muhammad Adlan Nur Abadia (Jurnal Zona, 2026)
The overpopulation of long-tailed macaques (Macaca fascicularis) on Lombok Island has led to human-wildlife conflicts that are detrimental to the agricultural sector, disrupt the balance of terrestrial ecosystems, and increase the risk of zoonoses. This research aims to identify the causes of overpopulation, analyze the ecological and socio-economic impacts, and formulate realistic ecology-based conservation strategies that support the achievement of Sustainable Development Goal (SDG) 15. The method used is descriptive qualitative with a case study approach, involving literature studies, contextual analysis of the Lombok region, and policy reviews. The research results indicate that wildlife feeding by tourists, habitat fragmentation due to land conversion, the high adaptability of the macaques, and the lack of natural predators are the primary causes of overpopulation. The resulting impacts include crop yield losses of up to 30-40% per season, habitat degradation, psychological distress among the community, and the potential transmission of zoonotic diseases such as rabies and herpes B. The recommended integrated conservation strategies include feeding bans, waste management, habitat restoration, limited sterilization, crop protection using wildlife-friendly infrastructure, compensation systems, and public education. These strategies directly contribute to SDG targets 15.5 (reducing habitat degradation) and 15.9 (integrating ecosystem values into regional planning). The conclusion of the study emphasizes that an integrated approach involving the community, government, and tourism operators is the key to the successful and sustainable management of human-wildlife conflicts in Lombok